Procalcitonin and Troponin-I as Predictor of Mortality in Acute Myocardial Infarction Patients - Novi Khila Firani; Jennifer Prisilla (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Acute Myocardial Infarction (AMI) is known as one of the leading causes of death in the world as well as in Indonesia. Procalcitonin is a marker of inflammation that has been recognized as a predictor of mortality in sepsis patients. The role of procalcitonin as a predictor of mortality in AMI patients has not been widely studied. Troponin-I has been recognized as a biomarker of AMI. It is unclear whether Troponin-I can also act as a biomarker to predict the death of AMI patients. This study aim is to determine the role of procalcitonin and troponin-I as predictors of mortality in AMI patients. A 5-month analytical observational study was performed on AMI patients who were admitted to Dr. Saiful Anwar, Malang. Patients with sepsis or infection were excluded. There were 51 study subjects, of whom median procalcitonin and troponin-I levels of patients who died were significantly different from survivors (p<0.05). Procalcitonin level with a cut-off of 2.16 ng/mL had a sensitivity of 77% and specificity of 87%. Troponin-I level with a cut-off of 3.1 ng/mL had a sensitivity of 61% and specificity of 84%. Odds ratio of procalcitonin to mortality was 17.78 (p=0.001), while troponin-I was not significant. Procalcitonin correlated with mortality (r= 0.519, p= 0.005). The conclusion of this research is procalcitonin acts as a predictor of in AMI patients.